A case study on utilizing geotextile tubes for tailings dams construction in China. Issue 2 (April 2019) - Yang, Yonghao; Wei, Zuoan; Cao, Guansen; Yang, Yan; Wang, Huan; Zhuang, Sunning; Lu, Ting
Abstract: This research presents a successful case, in which geotextile tubes have been used to construct a tailings dam for fine tailings disposal since 2008. Up to the end of 2016, the tailings dam raise has reached 9 m in height. The total height of the dam including the starter dike was 61 m. In order to ensure that the tailings reservoir is safe in its current condition and during future construction, the comprehensive geotechnical investigation and stability analyses of the tailings embankment are conducted in this study. The results show that the application of geotextile tubes in the construction of tailings dam is a good alternative for fine tailings disposal.